Targeting dairy interventions in Kenya: a guide for development planners, researchers and extension workers - Ouma, R.; Njoroge, L.; Romney, Dannie L.; Ochungo, P.; Staal, Steven J.; Baltenweck, Isabelle (International Livestock Research Institute, 2007)
This easy-to-use guide to effective targeting of selected dairy interventions in Kenya is intended for use by anyone involved in dairy farming in the country, such as development planners, researchers, service providers, suppliers of dairy inputs and extension workers. The guide answers the question often faced by these workers: where is their proposed intervention most likely to be adopted? Using a combination of Geographical Information Systems (GIS) mapping methods and economic regression techniques, this guide shows where and under what circumstances dairy technologies are most likely to succeed. The guide is divided into three sections. The first section deals with concepts, rationale and methodologies for targeting dairy interventions. It also explains, with examples, how to use the guide. The second section presents the targeting maps for various dairy interventions. A total of eleven dairy interventions are considered in this guide. For each, a map shows relative probability of adoption together with a description of the innovation and background information. Also presented are the socio-economic, biophysical and agro-climatic characteristics that predispose uptake of each intervention. The third section presents some policy-relevant research results in three topical areas: Cost of milk production; Evaluation and assessment of alternative milk preservation techniques; and Employment generation in the dairy marketing chain.